Daya saing sektor pertanian dalam mendorong pembangunan pertanian di Provinsi Jambi - Yulmardi Yulmardi; Erfit Erfit (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to look at the level of competitiveness of Jambi province in the agricultural sector and the necessary policy to increase competitiveness. The results of the study found that in large scale Jambi province has relatively high enough competitiveness in the agricultural sector, it can be seen from LQ coefficient of the agricultural sector is superior to one, especially in the fields of plantation and horticulture. Then, in the micro some commodities that potentially have relatively high competitiveness such as soybean, potato, chili, coffee and coconut commodities, especially if we look at the level of productivity, while rubber and palm oil mainly in terms of land area and production level. Then based on the SWOT analysis for the agricultural sector, it seems that the agricultural sector has the potential and opportunity to be developed in the future, which has obstacles and threats to the development of the agricultural sector. In order to increase the competitiveness of the agricultural sector for Jambi province, various policies were carried out including through improvement in terms of farmers' capabilities, institutions, productivity, production and cluster approaches.